REAKSI PASAR ATAS ISU PADA PERISTIWA ACCOUNTING RESTATEMENT - Nirmala Dewi, Dian (Jurnal Riset Akuntansi dan Keuangan, 2013)
Accounting restatement is used to be assumed as a negative signal in capital market. This research is aimed to find out market reaction to accounting restatement in Indonesia. Specifically, the objective of this research is not only for empirically investigating market reaction in general, but also for investigating the difference of market reaction based on issue of restatement. Using abnormal return and cumulative abnormal return as the proxy of market reaction, one sample and two sample independent t-test were run to reach the objectives. 63 samples were obtained from the restatement event during 2009-2012. While, event period were determined for 5 days around restatement date. The result shows that, in average, market positively react to accounting restatement. Further, the results indicate that market do not react differently within the issue of restatement.